Superconductor-antiferromagnet-superconductor π Josephson junction based on an antiferromagnetic barrier - Bulaevskii, Lev (2017)
We show theoretically that π Josephson junctions may be constructed by use of antiferromagnetic (AF) metals between superconducting electrodes. We argue that the AF magnetic ordering introduces the energy difference of electrons in a Cooper pair due to the effect of the exchange field varying in space. Such an energy difference is quadratic in the amplitude of exchange field and this is sufficient to change the behavior of a Josephson junction from 0 to π junction if the width of the AF metal is big enough. The advantage of using an AF barrier instead of a ferromagnetic one is that it does not suppress Cooper pairing in superconducting electrodes as much as the ferromagnet barrier does. However, to reach π -junction regime the AF metal should be a clean one with the electron mean free path bigger than the junction width.